A ZigBee-based elderly health monitoring system: design and implementation. (1st January 2014) - Talpur, Mir Sajjad Hussain; Liu, Wang; Wang, Guojun
Internet of Things and its associated innovative technologies such as ZigBee, wireless sensor network, radio frequency identification, smart technologies (robotics), distributed databases and energy saving technologies have huge potentials in remote healthcare monitoring system and medical services to augment aging citizens' living style, safety, healthcare services and also reshape the future of our healthcare environments. This paper explores the intended system to achieve elderly health monitoring system. The designed system obtains, transmits, stores and analyses the elderly physiological conditions for healthcare providers exactly in real time intrusive or non-intrusively through tiny human wearable multi-hop sensor network. Hence collaborative remote healthcare services to identify common or critical health problems, sickness symptoms and remote diagnosis. It also provides supportive healthcare service with indigenous assimilation and booming out efficient service to prevent chronic disease and edifice a robust elderly healthcare monitoring system with appraisal, inspiration and assurance, etc. It guarantees the elderly life of integrated care and comprehensive remote health information management. The proposed system primarily depends on Internet of Things, ZigBee, wireless sensor network, body sensors, web applications and databases.